rOral: use of a teledentistry system for remote images assessment in oral health education workflows - Sebastião, Raquel (2021)
Medical training in oral health includes interpreting images of the oral cavity. The use of extended datasets, real cases, and the ability to monitor the progress of students is beneficial. In this work, we investigate the feasibility of using a teledentistry solution to support medical training. The rOral integrated teledentistry solution, developed by the research team, allows the decoupling of image acquisition and image review: images of the oral cavity can be recorded using the camera of regular mobile devices, near the subject of care; the images are then uploaded to a secure storage and reviewed by experts, using a web environment. This workflow, primarily designed for remote oral health diagnosis (e.g.: population screening), can be used for dentistry education, allowing students to play the role of experts. A population of dentistry students was involved in the present study and used rOral to access anonymized cases to form a diagnosis. The results show that the existing solution, planned for remote diagnosis, is suitable for education and that smartphone-acquired images can be used in diagnosis assessment activities.